Polymer science and technology plastics, rubbers, blends and composites - Ghosh, Premamoy (McGraw-Hill Education LLC., 2011)
This book skillfully blends and integrates polymer science, plastic technology and rubber technology. The fundamentals of polymerization, polymer characteristics, rheology and morphology, as well as the composition, technology, testing and evaluation of various plastics, rubbers, fibres, adhesives, coatings and composites are comprehensively presented. New to this Edition ? Extensive discussion of dendritic polymers, dendrimers and useful inorganic polymers ? Lucid description of the use of power polymers in developing solar photovoltaic devices ? In-depth coverage of the applications of nanotechnology to polymers ? Detailed explanation of the use of polymers in waste disposal and recycling The book is highly suitable for all entrepreneurs and professionals engaged in production of as well as research and development in polymers. It will also be found immensely useful by advanced level students of physics, chemistry, materials science, and electronics specializing in polymers, as well as students of electronics, chemical and metallurgical engineering having courses in polymer technology/materials science and technology.